Non-timber forest products in the global context - Shackleton, S.; Shackleton, Charlie M.; Shanley, P. (Springer, 2011)
This book provides a comprehensive, global synthesis of current knowledge on the potential and challenges associated with the multiple roles, use, management and marketing of non-timber forest products (NTFPs). There has been considerable research and policy effort surrounding NTFPs over the last two and half decades. The book explores the evolution of sentiments regarding the potential of NTFPs in promoting options for sustainable multi-purpose forest management, income generation and poverty alleviation. Based on a critical analysis of the debates and discourses it employs a systematic approach to present a balanced and realistic perspective on the benefits and challenges associated with NTFP use and management within local livelihoods and landscapes, supported with case examples from both the southern and northern hemispheres. This book covers the social, economic and ecological dimensions of NTFPs and closes with an examination of future prospects and research directions.